Sodium Bromide-Catalyzed Oxidation of Secondary Benzylic Alcohols Using Aqueous Hydrogen Peroxide as Terminal Oxidant - Komagawa, Hiromi; Maejima, Yukako; Nagano, Takashi (Synlett, 2016)
A halide salt, hydroperoxide and AcOH catalyst system was applied to the oxidation of secondary benzylic alcohols. This simple system can be applied to a variety of secondary benzylic alcohols and scaled up for gram-scale preparation. High secondary benzylic alcohol selectivity of the present method is demonstrated in hydroxyketone synthesis. Based on several experimental results, a catalytic cycle for our oxidation is proposed.
Keywords: sodium bromide; bromine; oxidation; hydrogen peroxide; alcohol